New Testament Studies: 2004-: Editor's Perspective - Lieu, Judith (New Testament studies, 2004)
The editor of New Testament Studies is usually more than content to hide behind the impersonality of the role, protected by the corporate responsibility, if not identity, of the editorial board. For this, the 50th volume, however, an editorial postscript has been suggested, to balance the retrospective given by Professor C. K. Barrett at its start – although this is not designed to inspire more extensive searches for chiasms within the volume. It would take a braver, or more foolhardy, person than I, though, to label this a prospective, while it is, I must emphasise, written from a personal perspective and not as a signal of agreed editorial policy.